Valorization of Loads Petroleum by Thermal Process - Ben Tahar, N.; Mimoun, H. (Asian Journal of Chemistry, 2013)
This study was performed to allow the study of the chemical composition influence of the coking process load on the efficiency and the quality of coke. For this reason, the coking of the following loads was realized: Atmospheric residue, vacuum residue and catalytic residue of cracking. As the oil residues are rich for their strongly polar composition, such as the asphaltene resins and complex structures units, which has a role in the formation of coke and as the dispersion of these latter improves the quality of coke, a study on the stability of aggregation was carried out by the addition of one stabilizer (oil extract) in the coking process load. The compounding (extracted from/the residue of cracking oil) has been drived to the best efficiency of coke.